Who gets frustrated? Identifying individuals prone to frustration using a latent profile analysis - Yazdi, Hannaneh; Ljung Aust, Mikael; Wickman, Casper; Bujacz, Aleksandra; Kowalski, Leo; Lundström, Johan N. (Frontiers in Psychology, 2025)
IntroductionFrustration is a complex negative emotion with multifaceted components that significantly influence cognitive and behavioral responses. While previous studies have explored frustration, identifying distinct groups of individuals prone to frustration has yielded inconsistent findings. This study employs a person-centered approach to identify clusters of drivers based on frustration triggers and emotional responses to frustrating events.MethodsA total of 2,219 drivers participated in an online survey assessing frustration experiences in various frustrating scenarios. Latent Profile Analysis (LPA) was conducted to identify subgroups based on frustration triggers and emotional responses. Predictor variables included Driving Behavior Dimensions (violations, errors, and lapses), user group categories (car-sharing, ownership, leasing), and demographic factors (age and gender).ResultsLPA identified four distinct frustration profiles: Minimal, Low, Moderate, and Severe. These profiles were associated with different frustration triggers (i.e., goal blockage, limited control) and emotional responses (i.e., anger, stress, and irritation). The Severe profile, characterized by a high probability of individuals being highly prone to frustration, exhibited the highest frustration levels and was predominantly composed of older drivers (>45 years), particularly women, from car-sharing and leasing user groups. Emotional response patterns and the likelihood of frustration arousal are consistent across profiles, varying primarily in intensity.DiscussionThese findings offer insights into frustration susceptibility and underscore the need for targeted interventions to enhance emotion regulation in driving contexts. Future research should explore personalized strategies to mitigate frustration based on individual and group characteristics.